Comparative studies on thermoelectric properties of p-type Mg2Sn0.75Ge0.25 doped with lithium, sodium, and gallium. (December 2017) - Saparamadu, Udara; de Boor, Johannes; Mao, Jun; Song, Shaowei; Tian, Fei; Liu, Weishu; Zhang, Qinyong; Ren, Zhifeng
Abstract: Mg(Sn, Si) and Mg(Sn, Ge) are promising n-type thermoelectric materials with good thermoelectric properties in the temperature range of 300–800 K. For power generation, similar thermoelectric performance of p-type materials is equally important. However, p-type material performance is much worse than the n-type, because achieving optimized carrier concentration has been difficult for the p-type Mg2 X (X = Sn, Si). In this study we systematically compared the effect of the dopants Li, Na, and Ga and found that the highest carrier concentrations are achievable in Li-doped samples. Due to the relatively high content of Sn, carrier concentration of > 5 × 10 19 cm −3 were achieved for all dopants. Analysis of the transport data in the framework of a single parabolic band model showed similar and carrier concentration independent effective masses for all dopants. Our results therefore indicate a rigid band structure for p-type Mg2 X for the studied dopants, in contrast to previous reports. Higher carrier mobilities have been achieved for Li-doped samples compared to the previous reports. Larger Hall mobilities leads to a higher peak power factor. Due to the higher carrier concentration, the onset of intrinsic excitations (bipolar effect) effectively shifts to higher temperature compared to the other two dopants, which results in a peak figure of merit of ∼0.5 at 723 K for Li doped samples. Graphical abstract: Image 1